2014
DOI: 10.1007/s00339-014-8233-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative theoretical analysis of continuous wave laser cutting of metals at 1 and 10 μm wavelength

Abstract: We present a derivation and, based on it, an extension of a model originally proposed by V.G. Niziev to describe continuous wave laser cutting of metals. Starting from a local energy balance and by incorporating heat removal through heat conduction to the bulk material, we find a differential equation for the cutting profile. This equation is solved numerically and yields, besides the cutting profiles, the maximum cutting speed, the absorptivity profiles, and other relevant quantities. Our main goal is to demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…To develop the temperature history of the irradiated sample, the nondimensionalization method was introduced to track the changes due to each laser parameter, by calculating the non-dimensional temperature at the surface, depth, and center where the maximum non-dimensionaltemperature occurs [13]- [15]. This method is a simple technique for tracking the trend of changes occurring in laser irradiation, and is an effective step in investigating the effects of laser parameters upon the heat-affected profile [4] [16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To develop the temperature history of the irradiated sample, the nondimensionalization method was introduced to track the changes due to each laser parameter, by calculating the non-dimensional temperature at the surface, depth, and center where the maximum non-dimensionaltemperature occurs [13]- [15]. This method is a simple technique for tracking the trend of changes occurring in laser irradiation, and is an effective step in investigating the effects of laser parameters upon the heat-affected profile [4] [16].…”
Section: Methodsmentioning
confidence: 99%
“…Lasers are able to deliver a range of very low to extremely high energy with extreme precision in dimension, spatial, and temporal distribution. In comparison to conventional methods, this laser approach is more flexible and reduces processing time, making it particularly suitable for both mass production and rapid prototyping and custom-scale manufacturing for a wide variety of applications such as micro-welding, drilling, cutting, and heat treatment of metals and alloys [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Richter S et al [15] proposed the laser etching method of a micro-heat pipe composite groove, designed an orthogonal experiment to explore the influence of laser parameters on groove etching effect and optimized the laser etching process parameters of a micro-heat pipe composite groove. Brügmann et al [16] analyzed the temperature change in the process of continuous laser metal cutting by establishing a simulation model and studied the metal plate processing efficiency of different wavelengths of laser by process test. Aiming at the problem of laser etching of aluminum alloy sheet, Hui Zhang et al [17] analyzed the effects of laser power, laser cutting speed and gas pressure on laser etching mass, established an orthogonal experiment based on a singlefactor experiment and obtained the process parameter combination with the best etching effect.…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at the welding process of aluminum alloy parts, Tsirkasd et al [14] analyzed the change of temperature field in laser welding process by establishing three-dimensional finite element simulation model, and predicted the temperature of T-type laser welding plate during processing. Brügmann et al [15] analyzed the temperature change in the process of continuous laser metal cutting by establishing a simulation model, and the metal plate processing efficiency of laser with different wavelengths was compared through process test. Weng et al [16] found that the increase in laser power would increase the porosity and interface cracking sensitivity of the cladding layer.…”
Section: Introductionmentioning
confidence: 99%